The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1806-9282.62.07.701
|View full text |Cite
|
Sign up to set email alerts
|

Night eating syndrome: How to treat it?

Abstract: Night eating syndrome (NES) is characterized by caloric intake ≥ 25% of total daily after dinner and/or by two or more weekly nocturnal awakenings accompanied by food ingestion. Causes of NES are not entirely clear and seem to involve a desynchronization between the circadian rhythms of food ingestion and sleep, resulting in a delayed pattern of food intake. Estimates of the prevalence of NES in the general population are around 1.5%, and although much higher frequencies have been described in obese individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Treatments targeting the regulation of circadian rhythms, mood, stress, and faulty cognitions have been considered. Pinto et al [ 53 ] conducted a critical review of treatment for NES and concluded that serotonergic agents and psychological interventions, particularly cognitive behavioral therapy (CBT), have shown effectiveness [ 52 ]. However, Muscatello et al contends that there is still a paucity of research in this area, with treatment for NES remaining an emerging field [ 17 ••].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments targeting the regulation of circadian rhythms, mood, stress, and faulty cognitions have been considered. Pinto et al [ 53 ] conducted a critical review of treatment for NES and concluded that serotonergic agents and psychological interventions, particularly cognitive behavioral therapy (CBT), have shown effectiveness [ 52 ]. However, Muscatello et al contends that there is still a paucity of research in this area, with treatment for NES remaining an emerging field [ 17 ••].…”
Section: Treatmentmentioning
confidence: 99%
“…It is therefore thought to be connected to NES. Decreased serotonin levels have been hypothesized to lead to the alteration of circadian rhythms and increase risk of evening hyperphagia [ 53 ]. Night eaters have also been found to have higher levels of serotonin transporter in the temporal lobe, which contributes to changes in circadian rhythms and appetite [ 54 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This finding is consistent with that reported by Pinto et al and Rand et al, who estimated the prevalence of this condition to be 1.5% in the world. 1 , 20 In a study by de Zwaan et al, conducted on the general population in Germany, prevalence of NES symptoms was indicated at 1.1%. 21 Similar results were obtained in the study conducted by Zadjali et al on the population of Oman where the criteria of NES were fulfilled by 1.5% of the studied people.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological treatment. Serotonergic system, the main regulator of a wide variety of physiological functions and behaviors such as eating, sleep and mood is thought to be intrinsically involved in NES; mainly, a decrease in serotonin levels would lead to the alteration of circadian rhythms and to a high risk of evening hyperphagia and nocturnal eating (Allison et al, 2005a;Pinto et al, 2016;Stunkard et al, 2009a). Moreover, as previously reported, in night eaters higher levels of SERT in the temporal lobe have been documented (Lundgren et al, 2008b); this finding supports the presence of dysfunctions in postsynaptic serotonergic transmission, that contributes to changes in circadian rhythms and appetite (Stunkard et al, 2009b).…”
Section: Treatment Options For Nesmentioning
confidence: 99%